PENGEMBANGAN MODUL MATA KULIAH STATISTIKA DAN PROBABILITAS DENGAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MAHASISWA PROGRAM STUDI TEKNIK INFORMATIKA DI STMIK ASIA MALANG - Puji Subekti; Lilis Widayanti (FMIPA UNIVERSITAS NEGERI MALANG, 2017)
This research has the goal developing statistics and probability module based of Problem Based Learning which has the character of validity, practice, and effective for informatics engineering students. The module is developed using Plomp (2010) model. The steps of developing consist of (1) preliminary research, (2) prototyping phase, and (3) assessment phase by using validity questionnaire, practice questionnaire, pre-test and post-test. The result of the validity test obtains score 90.02%, the module having been very satisfy to use. According the result of practical test, the modul obtains average of score 87,5%. It means that the module is very practical and can be used in the instructional activity. The result of effectiveness test, by collecting students’ response, were got the average of score 86.33%. The average of 30 students’ pre-test and post-test obtains 69,83% and 86,17%. It is showed that the module is very effective. It means that the students are able to understand the module contents and the module can push the students’ learning motivation.Keywords: module, statistics and probability, Problem Based Learning, informatics engineering